Vesicular Stomatitis Virus-Based Vaccine Protects Mice against Crimean-Congo Hemorrhagic Fever - Rodriguez, Sergio E.; Cross, Robert W.; Fenton, Karla A.; Bente, Dennis A.; Mire, Chad E.; Geisbert, Thomas W. (Scientific reports, 2019)
Crimean-Congo hemorrhagic fever virus (CCHFV), a tick-borne bunyavirus, can cause a life-threatening hemorrhagic syndrome in humans but not in its animal host. The virus is widely distributed throughout southeastern Europe, the Middle East, Africa, and Asia. Disease management has proven difficult and there are no broadly licensed vaccines or therapeutics. Recombinant vesicular stomatitis viruses (rVSV) expressing foreign glycoproteins (GP) have shown promise as experimental vaccines for several viral hemorrhagic fevers. Here, we developed and assessed a replication competent rVSV vector expressing the CCHFV glycoprotein precursor (GPC), which encodes CCHFV structural glycoproteins. This construct drives strong expression of CCHFV-GP, in vitro . Using these vectors, we vaccinated STAT-1 knock-out mice, an animal model for CCHFV. The vector was tolerated and 100% efficacious against challenge from a clinical strain of CCHFV. Anti-CCHFV-GP IgG and neutralizing antibody titers were observed in surviving animals. This study demonstrates that a rVSV expressing only the CCHFV-GP has the potential to serve as a replication competent vaccine platform against CCHF infections.